PENGAKUAN DAN PENGUKURAN ASET BIOLOGIS SESUAI DENGAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 69 PADA CV X - Paula Merinatha Toprip, Halida Achmad Bagraff (Nsc Press, 2023)
The purpose of this research is to present the accounting treatments of biological assets is in accordance to Statement of Financial Accounting Standard Article 69 in CV. X, broiler farming. Accounting treatment in the agricultural business sectorneeds to be recorded with applicable standards so that it can present reliable financial reports for internal and external parties. The descriptive qualitative method is used in this research by collecting data, analyzing data, and interpreting data. The types of data used are primary and secondary data. The results of the study will be a description of the author to be used as a reference in measuring biological assets at CV. X so as to facilitate the transaction input process in the bookkeeping,balance sheets, income statements to cash flow statements.